PENGENDALIAN BIAYA DAN WAKTU DENGAN METODE EARNED VALUE ANALYSIS (EVA) PADA PROYEK JARINGAN IPAL KOTA PALEMBANG - Akbar, Muhammad Gumilar; Mulyati, Ely (Universitas Teuku Umar, 2024)
Abstract In executing a project, it is essential to maintain control to address any deviations, ensuring the project remains on schedule. Consequently, oversight and control measures must be implemented across all areas, particularly in terms of time and cost management. The Palembang City Wastewater Treatment Plant Network Project faced delays in its field operations, leading to discrepancies from the original timeline. In this context, the author will evaluate cost and time management using the Earned Value Analysis (EVA) method to assess performance and estimate the total cost and time needed for project completion, considering the delays. The EVA method serves as a comprehensive approach to manage project costs and schedules. The key parameters for this analysis are SEAC and BEAC. The SEAC indicates the projected duration necessary to complete the project, estimated at 918 days, while the BEAC reflects the total estimated cost for completion, amounting to Rp 210,078,454,167.97. The project's performance, evaluated through cost and time metrics via Earned Value Analysis, revealed unsatisfactory cost performance, as indicated by a negative CV value at the 25th month, the conclusion of the study, and a CPI of less than 1. This signifies that actual costs have exceeded planned costs, with negative SV and an SPI of less than 1, pointing to delays in the project. Keywords— Earned Value Analysis (EVA), Control, Cost, Time.